Afro-Colombian, discrimination and spatial segregation of employment quality for Cali (2016)
This article analyzes how race and geographical location affect the quality of employment of Cali's population. We estimate an ordered probit model based on information from the Survey of Employment and Quality of Life (SEQL) in Cali, implemented by the Ministry of Labour and the Municipality of Santiago de Cali, during November 2012 and January 2013. Our results show evidence of possible racial discrimination of the Afro-Colombian population in Cali. Likewise, there is evidence of possible spatial segregation of employment quality, because even in the same city, employment quality varies depending on the area of residence.